ANALISA SUDUT PANDANG CIVITAS AKADEMIKA TERHADAP KEAHLIAN AKUNTAN BERBASIS FORENSIK (STUDI EMPIRIS PADA CIVITAS AKADEMIKA STIE CENDEKIA KARYA UTAMA SEMARANG) - Sugiarto; Yulia Kusumaningrum (E-logis : Jurnal Ekonomi Logistik, 2022)
This study aims to analyze the differences in perceptions between accounting lecturers, accounting students, and education staff regarding deductive analysis skills, critical thinking, solving unstructured problems, investigative flexibility, analytical skills, oral communication, written communication, knowledge of law, and a calm attitude. Is a relevant part of the forensic accountant’s expertise. The research objects are accounting lecturers, accounting students, and educational staff. This research is an empirical study with purposive sampling technique in data collection. Data were obtained by distributing questionnaires as many as 37 at STIE Cendekia Karya Utama Semarang consisting of 11 accountig lecturers, 16 accounting students, and 10 education staff who have provided answers. Data analysis was performed using the Independent Sample Test with the SPSS program. The results of hypothesis testing show that there is no significant difference in perceptions between accounting lecturers, accounting students, and education staff on flexibility skills, wtitten communication skills, ang legal knowledge. The results of hypothesis testing show that there are significant differences in perceptions between accounting lecturers, accounting students, and education staff on deductive analysis skills, critical thinking, problem solving, analytical skills, oral communication and being calm